Post-Traumatic Stress Disorder Among ICU Survivors - Roshna Vadakkedath; Sherin Susan Thomas (RGUHS Journal of Nursing Sciences)
Post-traumatic stress disorder PTSD can occur following an exposure to a stressful event that poses a threat to the life. The personrsquos reaction to this event includes intense feeling of fear helplessness and variety of psychological and behavioral symptoms. Evidence shows that a stay in an intensive care unit ICU is a traumatic experience leading to ICU survivors developing PTSD. A literature review was done across PubMed Google scholar SCOPUS. ICU survivors post-traumatic stress disorder were the keywords used for the search. The overall prevalence of PTSD among ICU survivors ranged between 3.7 - 43.7. The most commonly observed features included nightmares memories of the trauma hypervigilance irritability emotional withdrawal poor concentration and difficulty sleeping. Some individuals also experienced depression 32 and anxiety 38 in conjunction with PTSD. Management of PTSD among ICU survivors includes pharmacological as well as non - pharmacological interventions. The article concluded that PTSD among ICU survivors vary significantly and this condition is common with symptoms of post-traumatic stress potentially lasting for several months following recovery from critical illness.